Non-HDL-C in Conjunction to LDL-C is associated with Incidence of Chronic Coronary Syndrome in Clinical Settings - Mayasari, Ni Made Elva; Rosita, Yanti; Olivia, Sindy (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Background: The biggest cause of death and a major contributor to disability globally is coroner's artery disease (CAD).  Chronic coronary syndrome (CCS) is a term that can be used to describe a wide variety of CAD clinical manifestations in clinical settings. Non-HDL-C is advised as a routine component of lipid analysis for risk assessment in patients with elevated plasma TGs. Conflicting results have been yielded as Non-HDL-C is a better marker comparing LDL-C.Objective: The purpose of this study is to find out the relationship of Non-HDL-C levels with the incidence of CCS in conjunction with LDL-C testing in a clinical setting. Methods: Observational analytical research with a cross-sectional design was conducted in Muhammadiyah Palembang Hospital from October to December 2019. Simple random sampling techniques were used to select 89 patients who met the study's inclusion and exclusion criteria. Non-HDL-C and LDL-C calculations based on routine lipid testing. The Chi-Square test with a significant p-value <0,005 was used for bivariate analysis.Results: There is a statistically significant association between non-HDL-C levels and the incidence of CCS (p=0,001), as well as a significant association between LDL-C and CCS incidents (p=0,009).  Conclusion: Non-HDL-C provide additional benefits in identifying CAD risk factors in outpatients with CCS patient as well as LDL-C